Potential Adverse Cardiovascular Effects of Treatment With Fluoxetine and Other Selective Serotonin Reuptake Inhibitors (SSRIs) in Patients With Geriatric Depression: Implications for Atherogenesis and Cerebromicrovascular Dysregulation - Ungvari, Zoltan; Tarantini, Stefano; Yabluchanskiy, Andriy; Csiszar, Anna (Frontiers in Genetics, 2019)
Late life depression is an important public health problem, which associates with increased risk of morbidity and mortality. Fluoxetine is a potent selective serotonin re-uptake inhibitor (SSRI) drug, which is often prescribed to treat geriatric depression. There is increasing evidence that fluoxetine exerts a wide range of cardiovascular side effects, which are unrelated to the ability of the drug to inhibit serotonin receptors. Furthermore, there is evidence that aging may increase plasma level of fluoxetine and its active metabolite, norfluoxetine. In this overview, the potential role of side effects of fluoxetine treatment in the pathogenesis of age-related cardiovascular diseases, including atherogenesis, cardiac pathologies and cerebromicrovascular impairment is discussed.